Prevalence, severity and distribution of depression and anxiety symptoms using observational data collected before and nine months into the COVID-19 pandemic - Duncan Thomas; Ralph Lawton; Tyson Brown; Rachel Kranton (Elsevier, 2021)
Background: The COVID-19 pandemic has been accompanied by substantial increases in adverse mental health, particularly among the young. However, it remains unclear to what extent increases in population scores on mental health assessments are due to changes in prevalence, rather than severity of symptoms. Further, it is not obvious that widely used assessments of aggregate symptoms retain their typical interpretation during an event that directly disrupts behavior. Methods: Pre-pandemic data on workers age 18-69y in the 2019 National Health Interview Survey are reweighted to match distributions of demographic characteristics of Duke University employees surveyed nine months into the pandemic. The latter population was at low risk of infection or economic insecurity. Prevalence, severity, and scores for each of nine symptoms are compared overall and by age group. Outcomes: Elevated psychological distress is primarily driven by increases in prevalence of particular symptoms. Prevalence of trouble concentrating increased six-fold from 9.6% to 72.5%. Other symptoms increased by over one-third; feeling anxious, having little interest, feeling depressed, sleep problems and being irritable, while some symptoms rose only 10% or less. Severity also increased but magnitudes are small relative to prevalence changes. Escalation in prevalence and severity are greatest for the youngest. Interpretation: Some of the least prevalent symptoms pre-pandemic became the most prevalent during the pandemic, affecting interpretation of indices validated pre-pandemic. Clinical and policy interventions should focus on specific symptoms that increased including trouble concentrating and anxiety. Funding: Trinity College of Arts & Sciences and Social Science Research Institute at Duke University.